Improving the Switched Split Vector Quantization Technique using a Joint Source Channel Coding Approach - Tran, Ngoc Tuan; Nguyen, Quoc Trung; Tran, Hai Nam (Old Journal, 2017)
This paper deals with enhancing the error resilient of the Switched Split Vector Quantization (SSVQ) techniques by adopting the optimal Index Assignment approach, a Joint Source-Channel coding method. SSVQ is one of the latest structured vector quantization schemes and it has several advantages over other schemes. The new method proposed in this paper can improve the SSVQ encoder without the addition of extra bits and coding complexity. In addition, the application of the new method in speech coding is also investigated in this paper. The effectiveness of IA-SSVQ method is validated by comparing it with other methods through simulations.